1983
DOI: 10.1037/0096-3445.112.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Attentional processing and the subjective contour illusion.

Abstract: Leading explanations of the subjective contour illusion can be classified as being either "bottom-up" or "top-down." Bottom-up explanations assert that peripheral, physiological mechanisms often associated with the perception of real contours also account for subjective contour (SC) perception. In contrast, top-down explanations posit a more central locus of SC perception and are formulated on a molar, psychological level. A major aspect of bottom-up perceptual processing is that it is largely automatic. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 53 publications
2
29
1
Order By: Relevance
“…Adding lines to our illusory contours always increased the masking magnitude. Second, the perception of illusions as illusions takes time (on the order of 100 msec; Reynolds, 1978) and the perception of illusory contours apparently requires effortful attention (Pritchard & Warm, 1983). One way of assessing whether naive subjects are perceiving illusory contours is to establish whether they see depth separationor a brightnesschange (Parks & Prendergrass, 1982;Rock & Anson, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Adding lines to our illusory contours always increased the masking magnitude. Second, the perception of illusions as illusions takes time (on the order of 100 msec; Reynolds, 1978) and the perception of illusory contours apparently requires effortful attention (Pritchard & Warm, 1983). One way of assessing whether naive subjects are perceiving illusory contours is to establish whether they see depth separationor a brightnesschange (Parks & Prendergrass, 1982;Rock & Anson, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of a texture segmentation task, Meyer and Fish (1987) have reported similar findings. Comparing the times required to discriminate between different shapes of edge-induced illusory forms and between equivalent outlined forms, Pritchard and Warm (1983) found that reaction times increased more for illusory form discrimination than for outlined form discrimination as attentional loads were increased, implying a greater attentional demand for illusory contour perception. The high attentional demand indicated by these experiments has been used to argue for a cognitive theory of illusory contour formation.…”
Section: High-level Determinantsmentioning
confidence: 99%
“…The salience of the illusory contour varied as a function of time, apparently indicating time-varying cognitive hypotheses regarding the relative depths of the inducers, overlayed pattern, and illusory figure. Additional support for this form of cognitive theory comes from the perception of reversible and ambiguous illusory figures (Bradley, 1982(Bradley, , 1987Bradley,Dumais, & Petry, 1976),the effects ofleaming and memory on contour perception (Coren et aI., 1986(Coren et aI., , 1987Gellatly, 1982;Gellatly & Bishop, 1987;Landauer, 1978;Pritchard & Warm, 1983;Wallach& Slaughter, 1988), and other time course studies (Meyer & Fish, 1987;Pomerantz, Goldberg, Golder,& Tetewski, 1981;Takahashi, 1993).…”
Section: Cognitive Theoriesmentioning
confidence: 99%
“…If subjective contours are computed in a bottom-up, or reflexive, fashion, then they should exhibit the characteristics of preattentive processes (Neisser, 1967). Namely, their detectability should not be influenced by concurrent, nonvisual task requirements (Pritchard & Warm, 1983), they should show spontaneous segregation in a texturediscrimination task (Beck, 1982;Julesz, 1984), and they should be detected in parallel in a visual-search task (Treisman & Gelade, 1980). Recent evidence indicates that subjective contour perception demonstrates none of these characteristics (Grabowecky & Treisman, 1989;Meyer & Fish, 1987;Pritchard & Warm, 1983).…”
Section: Visual Searchmentioning
confidence: 99%
“…Dual Task Procedures Pritchard and Warm (1983) examined whether form discrimination based on Kaniza-like subjective contours versus real contours was differentially affected by attentionalload. They found that without attentionalload there was no significant difference in the speed with which same-different judgments could be made between forms defined by real or subjective contours.…”
Section: Visual Searchmentioning
confidence: 99%